Analisis Pengaruh Penambahan Lumpur Gambut Terhadap Penurunan Kekeruhan, Zat Organik, Dan Warna Air Gambut Dengan Cara Koagulasi Menggunakan Koagulan Aluminium Sulfate (Al2(SO4)3) - Assi Syura; Dewi Fitria; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat water is a surface water that’s found in swamp and lowland areas that have characteristics of organic matter, turbidity and high color. One of peat water treatment that can be used by coagulation-flocculation. This study aims to determine the effect of peat sludge addition in coagulation-flocculation process with Coagulant Aluminium Sulfate (Al2(SO4)3) 1%. Peat water was taken in Rimbo Panjang Village, Tambang District, Kampar Regency, Riau Province. Peat sludge used in this study amounted to 6.7 gr/L, 13.4 gr/L, 20 gr/L. 26.7 gr/L and 33.4 gr/L. Rapid stirring that used 250 rpm during 1 minute and slow stirring at 60 rpm, 40 rpm and 20 rpm every 20 minutes. The results of this researchshowed that the value of turbidity increased by 18.77% with allowance efficiency from 70.45% to 89.22%, organic substance efficiency increased by 3.84% with efficiency from 96.03% to 99.87% and color efficiency parameters increased by 1.36% with efficiency from 98.50% to 99.86%.Keywords: Peat Water, Coagulation-Floculation, Peat Sludge, Turbidity, Organic Substances, Color